Selinexor in acute myeloid leukemia: therapeutic applications and current challenges - Qie, Ziyu; Ma, Li; Tan, Jie; Peng, Xiaochun (Frontiers in Pharmacology, 2025)
This article aims to review the current application status and research advancements of selinexor in the treatment of acute myeloid leukemia (AML). Selinexor, as the first oral selective inhibitor of nuclear export protein Exportin-1 (XPO1), inhibits the abnormal nuclear export of tumor suppressor proteins by blocking XPO1, thereby restoring their activity and exerting antitumor effects. Clinical studies have shown that selinexor monotherapy or combination therapy has demonstrated good anti-leukemia effects in AML, especially in patients with relapsed/refractory AML. In addition, the combination of selinexor with other drugs, such as demethylating agents and FLT3 inhibitors, has shown synergistic antitumor effects. Although selinexor has shown potential, its resistance and adverse reactions still need further research and control. Future research directions include exploring the best medication schemes, clarifying the appropriate population, and developing new combination treatment plans to improve treatment effects and overcome drug resistance issues.